The impact of emotional intelligence on the job effectiveness of private university lecturers - Ahmad Shah, Norliana; Saad, Mazni; Mohamad Mohan, Noor Malinda; Poniran, Halimi (Academic Inspired Network, 2018)
The emotional quotient or intelligence (EQ) is one of the essential concepts, which was recently introduced to the psychology and management in education line. Thus, the purpose of this study is to examine the impact of EQ on private university lecturers’ job effectiveness. The fundamental objective is to explore the EQ of the private universities’ lecturers and examine how it predicts their job effectiveness beyond the ability. A list of private universities in Selangor was short-listed; however, only five universities gave positive response to participate in the survey. The cross-sectional data collection was done within a month, and 127 usable data were analysed by using the IBM-SPSS. The results demonstrated that EQ significantly affects job effectiveness of the lecturers. However, only self-regulation and social skill are statistically significant, with selfregulation variable represents the strongest unique contribution to explain the job effectiveness. The findings of the study suggest that employees can apply their personal emotional experience into their work well. Also, it helps them to develop strong emotional bonding with those people associated with their work and leads to organizational performance. Hence, it is particularly imperative for a private university to use EQ to predict job effectiveness.